Immobilization and Characterization of Serum Albumin in SBA-15 Mesoporous Material - Zhai, Qing-Zhou; Wei, Yu-Chen; Wang, Qing-Shuan (Asian Journal of Chemistry, 2012)
Bovine serum albumin was immobilized inside SBA-15 mesoporous silica through physical adsorption method. Chemical analysis, powder X-ray diffraction, Fourier transform infrared spectroscopy, low-temperature N2 adsorption-desorption at 77 K, scanning electron microscopy, high resolution transmittance microscopy, ultraviolet-visible solid diffusion reflection spectroscopy and luminescence spectroscopy were used to characterize the prepared (SBA-15)-bovine serum albumin hybrid material and luminescent spectrum of the hybrid composite material was studied. The results showed that the guest bovine serum albumin had already been encapsulated in the host molecular sieve and its immobilization amount was 72.99 mg/g (BSA/SBA-15) and bovine serum albumin had partially come into molecular sieve pore channels and the molecular sieve framework in composite material was remained intact. The ultraviolet-visible solid diffusion reflection spectra indicated that absorption peak of the composite material brought an obvious blue shift compared with that of bovine serum albumin, showing that the bovine serum albumin was already assembled in the channels of molecular sieve. The average particle diameter of (SBA-15)-bovine serum albumin sample measured from SEM was 345 ± 10 nm. Blue light of hybrid material (SBA-15)-bovine serum albumin was emitted at 439 nm.